SOX2, PIWI proteins, and MALAT1 - plasma-based emerging biomarkers for cancer detection and monitoring. - Ekaterina Kldiashvili; Ivane Abiatari; Elene Kekelia; Saba Iordanishvili; Tornike Metreveli; Eter Dumbadze (PLoS ONE)
Background SOX2, PIWI proteins, and MALAT1 are molecular regulators implicated in cancer progression, proliferation, and epithelial-mesenchmal transition (EMT). This study evaluated their expression in plasma samples from patients with colorectal, breast, and prostate cancers, and assessed their correlations with standard immunohistochemical (IHC) markers. Methods A total 300 participants were enrolled: 150 patients with histologically confirmed cancers (50 colorectal cancer, 50 breast cancer, and 50 prostate cancer cases) and 150 age- and sex-matched healthy controls. Plasma RNA and protein levels of SOX2, PIWIL1, PIWIL2, and MALAT1 were measured via quantitative real-time polymerase chain reaction (qRT-PCR) and enzyme-linked immunosorbent assay (ELISA), respectively. IHC scores (Ki-67, p53, E-cadherin, vimentin, estrogen receptor/progesterone receptor, human epidermal growth factor receptor 2, androgen receptor) were retrieved from clinical records. Receiver-operating characteristic curve (ROC) analysis, multivariable logistic regression (adjusting for age and sex), and Pearson's correlation coefficients were used to evaluate biomarker diagnostic performance and tumor marker associations. Results SOX2, PIWI proteins, and MALAT1 were significantly elevated in cancer patients versus controls (p < 0.001), with qRT-PCR and ELISA results strongly correlated. All three biomarkers showed strong positive correlations with Ki-67 (r = 0.65-0.72, p < 0.001), and MALAT1 was associated with EMT marker changes (↓E-cadherin, ↑ vimentin; p < 0.001). Adjusted ROC analysis yielded area under the curve (AUC) values of 0.82-0.89 for individual biomarkers, with sensitivity ranging from 72-84% and specificity from 75-87%. SOX2 levels showed significant correlations with Ki-67 and p53 IHC positivity in colorectal and breast cancer tissues (p < 0.01), although the functional significance of p53 staining remains inconclusive. Conclusion The differential expression of SOX2, PIWI proteins, and MALAT1 between cancer patients and healthy controls supports their potential utility as plasma-based biomarkers for distinguishing cancer cases from non-cancer cases. These findings support their potential utility as non-invasive biomarkers for distinguishing cancer cases from healthy individuals.